Water security decision-making issues in Central Asia - Prniyazova А.Е.; Dalelkhan А.; Gusseinova Х. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The article is devoted to the study of the sources of endogenous uncertainty in water resources management on the example of the Central Asian states. The study focuses on endogenous uncertainties arising in the decision-making system and identifies key factors for their mitigation, including data availability and analysis, sustainable infrastructure and expanded capacity. The study recognizes the potential increase in exogenous uncertainty caused by limited cross-border cooperation, the effects of climate change and the growing need for water. He emphasizes the importance of recognizing and understanding the nature and consequences of uncertainties. Thus, the Central Asian countries can make more informed decisions and work towards achieving sustainable water security in the region. In the Central Asian republics, water security is becoming increasingly important due to the uncertainty and risks associated with climate change and the growing demand for water. This is compounded by growing disputes over important complex transboundary river basins, interconnected water and energy infrastructure in the Aral Sea basin, water distribution between riparian countries and the vulnerability of water resources to climate change. It is assumed that the adoption of effective decisions at all levels concerning the allocation and management of water resources will contribute to achieving water security.